The Efforts to Minimize Discipline Violations of Elementary School Students in the Application of Punishment - Musiman, Musiman; Hadiwinarto, Hadiwinarto (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is in the form of a quantitative descriptive that analyzes data based on numbers or percentages in analyzing the data that is the sample and the population in this study is all PAI teachers, principals, and students as many as 65 people. So the number of samples from this study was 25 people consisting of 20 students of class V (Five), 1 principal, and 7 teachers at SDN 2 Madang OKU Timur. The results of the study are that not all teachers at SDN 2 Madang OKU Timur agree with the application of educational punishment. The implementation of punishment at SDN 2 Madang OKU Timur is punishment in the form of delay in giving awards, punishment in the form of revocation of student privileges, expulsion from class or time out, punishment in the form of suspension. Meanwhile, the obstacles faced by teachers in implementing educational punishment for violations of student discipline at SDN 2 Madang OKU Timur were the lack of support from parents for the implementation of educational punishment, the difficulty of understanding the character of children, and the pros and cons among teachers at SDN 2 Madang OKU. East.